Biology of the invasive shell lerp psyllid, Spondyliaspis cf. plicatuloides (Froggatt) (Hemiptera: Aphalaridae) - Makunde, Privilege; Slippers, Bernard; Bush, Samantha; Hurley, Brett (African Entomology, 2023)
Spondyliaspis cf. plicatuloides (Froggatt) (Hemiptera: Aphalaridae) is native to Australia but was first detected outside its native range in 2014, in South Africa. It feeds on eucalypt species and thus has the potential to become a pest in commercial Eucalyptus plantations. Information on the basic biology of this insect, which is important for the development of surveillance and management strategies, is lacking. To investigate the life cycle and general biology of S. plicatuloides, the psyllid was reared under controlled glasshouse conditions on potted red-flowering gum, Corymbia ficifolia. The egg incubation period, number of nymphal instars and their developmental time, adult fecundity, adult longevity and duration of the life cycle were determined. The major diagnostic features used to differentiate the five nymphal instars were the number of antennal segments, wing pad development and body length. Females reached reproductive maturity 2.3 ± 0.47 (mean ± SD) days after eclosion and laid 16.2 ± 3.9 (mean ± SD) eggs on average. Reproduction was sexual. The first nymphal instar took 10.7 ± 1.2 (mean ± SD) days to hatch from the egg. The nymphal instars completed their development in 22.6 ± 1.4 (mean ± SD) days under the brown scalloped shelters they secrete. The insect's total life cycle lasted 37.37 ± 1.17 (mean ± SD) days from egg to adult death. Males and females lifespan is also reported. The study provides the first information on the basic biology of S. cf. plicatuloides that will be useful for future studies on surveillance and management strategies.